PENGETAHUAN DAN SIKAP PASIEN COVID-19 YANG MENJALANI ISOLASI MANDIRI TERHADAP PERILAKU PENGELOLAAN LIMBAH - Havivi Dwi Anggraeni; Yuni Wijayanti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2022)
Based on the data up to September 2021, Covid-19 patients who run in isolation in Garung District increased untill 81 people. The handling of the Covid-19 patient who are self-isolating risk to transmit Covid-19 through waste management. The purpose of this study is to find out how the picture and relationship of the level of knowledge and attitude of Covid-19 patients in self-isolation to infectious solid waste management behavior in Garung District in 2021.The study used a Cross Sectional design. The population in this study is all self-isolation patients in Garung District which amounted to 81 people with a sample of 42 people. The instrument used is a questionnaire sheet. Data analysis uses univariate analysis and bivariate analysis with SPSS applications. The results of the univariate analysis showed that the level of knowledge Covid-19 patients who are self-isolating in Garung District was in the good category (57.1%), and the attitude had in the category was quite good (61.9%). Infectious solid waste management behavior when self-isolation in the category is quite good (59.6%). The results of the bivariate analysis showed that there was a significant relationship between knowledge level (p =0.000) and attitude (p=0.032) with infectious solid waste management behavior in Covid-19 patients who are self-isolation in Garung District in 2021.